No pets allowed? Companion animals, older people and residential care. Issue 2 (9th July 2019) - Fox, Marie; Ray, Mo
Abstract : This article is concerned with a particular site of inter-species relationships. Using the lens of liminality, it examines forced separation of older people from their companion animals when they move to a residential or nursing home in the UK. Such residential spaces frequently either exclude companion animals or fail to make adequate provision for them to accompany their human caretakers. We see such separation as a major bereavement for an older person at a stage of life when they experience significant other losses, and suggest it is often experienced as akin to the loss of a family member. We deploy vulnerability theory to argue that exclusion of companion animals from care spaces exemplifies a failure to understand the relational vulnerabilities of older age and the significance of animal companionship in mitigating those vulnerabilities. Equally, such separation fails to recognise the implications for excluded animals who can end up in unsuitable homes, being signed over to already over-stretched animal rescues or euthanised. Vulnerability theory highlights how companion species are always already vulnerable, given their liminal position between person and property, while older people are rendered particularly vulnerable in the 'liminal zone' of the care home, denied the ability to shape their environment, control their private space or form/sustain relationships of their own choosing. This article explores the potential of law to respond to and mitigate these shared vulnerabilities, suggesting that human rights arguments grounded in shared vulnerability may be invoked to argue for a re-definition of the family to recognise the significance of the human–animal relationship. We draw on the reasoning in a recent Court of Protection case which hints at law's ability to recognise the value of interspecies relations and their role in sustaining health and well-being, and the ability to live well in old age.